Interleukin-37 expression and its potential role in oral leukoplakia and oral squamous cell carcinoma - Lin, Lin (Sci Rep, 2016)
Interleukin 37 (IL-37) has been reported to play a significant role in innate immune response and to be involved in several kinds of cancers. However, the investigation of association between IL-37 and oral mucosa carcinogenesis hasn't been clearly established. The aim of the study was to assess IL-37 expression and explore its role in oral mucosa carcinogenesis. The expression of IL-37 increased from normal control (NC) to Oral leukoplakia (OLK) and oral squamous cell carcinoma (OSCC). Moreover, statistically highly significant difference was present between scores of OLK with and without mild/moderate dysplasia (P < 0.001). In addition, IL-37 expression was lower in OSCC with lymph node metastasis than those without metastasis (P < 0.01). What’s more, overexpression of IL-37 in RAW264.7 cells remarkably reduced the pseudopodia, vacuolization and the expression of IL-6, TNF-α, and IL-1β. Finally, we found IL-37 and its receptor IL-18Rα but not its binding partner IL-18BP have similar tissue location and expression trend in different stages of oral mucosa carcinogenesis. Overall, IL-37 can be used as a biomarker for early oral tumorigenesis and for malignant transformation risk assessment of premalignant lesions.